2021
DOI: 10.1126/sciadv.abd9732
|View full text |Cite
|
Sign up to set email alerts
|

TRIM26 is a critical host factor for HCV replication and contributes to host tropism

Abstract: Hepatitis C virus (HCV) remains a major human pathogen that requires better understanding of virus-host interactions. In this study, we performed a genome-wide CRISPR-Cas9 screening and identified TRIM26, an E3 ligase, as a critical HCV host factor. Deficiency of TRIM26 specifically impairs HCV genome replication. Mechanistic studies showed that TRIM26 interacts with HCV-encoded NS5B protein and mediates its K27-linked ubiquitination at residue K51, and thus promotes the NS5B-NS5A interaction. Moreover, mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…Since viral genomes have a limited coding capacity, DNA/RNA viruses often hijack cellular factors to promote their proliferation in host cells. It was reported that TRIM26, an E3 ligase, was a critical host factor for hepatitis C virus (HCV) replication and contributed to host tropism ( 20 ). There is also evidence that HSV-1 hijacks cofilin to facilitate virus entry into neuronal cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since viral genomes have a limited coding capacity, DNA/RNA viruses often hijack cellular factors to promote their proliferation in host cells. It was reported that TRIM26, an E3 ligase, was a critical host factor for hepatitis C virus (HCV) replication and contributed to host tropism ( 20 ). There is also evidence that HSV-1 hijacks cofilin to facilitate virus entry into neuronal cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typical examples include screens to identify coding genes conferring resistance to a drug, toxin, pathogen, or immune cells (Guo et al, 2022;Liang et al, 2021;Peng et al, 2015;Ren et al, 2015;Shalem et al, 2014;Zhao et al, 2019;Zhou et al, 2014;Zhu et al, 2021). In a positive screen, the majority of cells are depleted under strong selection conditions, and only a few cells with a protective phenotype expand.…”
Section: Crispr Screen Pipelines and Strategiesmentioning
confidence: 99%
“…However, another study reported that TRIM26 actually enhanced innate immunity against RNA viruses, by recruiting NEMO to facilitate the interaction between TBK1 and MAVS ( 66 ). Furthermore, a genome-wide CRISPR-Cas9 screening identified TRIM26 as a critical HCV host factor, where it mediates K27-linked ubiquitination of HCV-encoded NS5B protein, enhances the interaction between NS5B-NS5A, and ultimately promotes HCV genome replication ( 67 ). Thus, as a key E3 ubiquitin ligase, TRIM26 plays multiple roles through catalyzing the conjugation of multiple ubiquitin chains to variety of substrates.…”
Section: Emerging Roles Of Mhc-i Region Encoded E3 Ubiquitin Ligases In Innate Immunitymentioning
confidence: 99%